The Effect of Leverage on Financial Distress: Liquidity as a Moderating Variable in Transportation and Logistics Companies 2020–2024 - Regita Purwaningsih; Krisdiana (International Journal of Business, Economics, and Social Development, 2026)
This research seeks to examine how leverage influences financial distress while considering liquidity as an interaction variable among transportation and logistics firms listed on the Indonesia Stock Exchange during 2020–2024. The background of this research is the high capital intensity and debt dependency within the sector, which can heighten the probability of financial distress, especially when liquidity management is not carried out effectively. Companies in the transportation and logistics sector generally require substantial capital to support operational activities, infrastructure development, and fleet procurement, which often leads to a high reliance on external financing sources such as debt. When the proportion of debt becomes excessive and is not balanced with adequate liquidity, companies may experience difficulties in meeting their short-term and long-term obligations, increasing the risk of financial distress. This study uses a quantitative research approach with purposive sampling criteria, resulting in 11 companies and 39 annual financial statement observations during the research period. The data were analyzed using multiple regression analysis and moderated regression analysis (MRA) with the assistance of SPSS software to examine the interaction effect of liquidity in the relationship between leverage and financial distress. The findings indicate that leverage has a positive influence on financial distress, implying that higher levels of debt increase the likelihood of companies experiencing financial difficulties. Liquidity also shows a positive relationship with financial distress and strengthens the relationship between leverage and financial distress as a moderating variable. These findings provide practical implications for managers and investors in determining optimal capital structures and improving liquidity management to reduce financial risk and maintain company stability.